'Corpore sano in mens sana'. The Morality of Blood Donation - Casado Neira, David (Athenea Digital, 2006)
Modern conceptions of health separate body from soul in the familiar Cartesian dualism. In blood donation this separation is easy to identify: embodiment is a civilizing process, and altruism is the moral basis that supports it. The donor is treated as essentially a vessel of blood, a mere container which can be directed to discharge its contents into blood banks. The biomedical use of blood is not morally neutral; indeed, the donor's moral conscience is mobilised in order to get them to donate blood as a gift, or offering. By associating donors' altruism with their bodies' physical nature as a container from which blood can be extracted, altruism is treated as a physiological phenomenon.